PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUNSCREEN UNTUK LAKI-LAKI DENGAN JENIS KULIT SENSITIF - Ashara, Rahma; Widagdo, Bambang Wisnu (PT Triputra Sejahtera Prima, 2024)
Skin health is an important aspect that requires protection from UV exposure. While skincare is more commonly associated with women, it's important to remember that men need skincare too. However, men's reluctance to talk openly about their skincare products is an obstacle in choosing a suitable sunscreen product. Skin has various types, especially sensitive skin types that require special attention. The sunscreen selection process still uses a manual method by checking the packaging and then comparing them one by one without considering specific criteria, potentially resulting in a sunscreen that is not suitable for sensitive skin and user needs. To help reduce errors and provide convenience in choosing sunscreen products for men with sensitive skin, a decision support system is made with the Simple Additive Weighting (SAW) method. In this study, the authors considered five sunscreen products by taking into account eight relevant criteria. The results showed that products with codes A2 (Parasol Face Sunscreen 33 SPF) and A4 (LRP Anthelios UVMune 400 Invisible Fluid SPF 50+) had the highest value, which was 0.9999, so they were considered the best results.